Proceedings of the 4th Symposium on Usable Privacy and Security 2008
DOI: 10.1145/1408664.1408666
|View full text |Cite
|
Sign up to set email alerts
|

Improving text passwords through persuasion

Abstract: Password restriction policies and advice on creating secure passwords have limited effects on password strength. Influencing users to create more secure passwords remains an open problem. We have developed Persuasive Text Passwords (PTP), a text password creation system which leverages Persuasive Technology principles to influence users in creating more secure passwords without sacrificing usability. After users choose a password during creation, PTP improves its security by placing randomly-chosen characters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(87 citation statements)
references
References 20 publications
2
84
0
1
Order By: Relevance
“…However, the mean login time was 19 seconds (by the end of Lab Session 2). To place this time in context, we compare it to Forget et al [9], who reported login times for 8-character text passwords as well as Persuasive Text Passwords (PTPs). 2 In the PTP variant that provided the optimal combination of security and usability, the login time was 17.1 sec.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…However, the mean login time was 19 seconds (by the end of Lab Session 2). To place this time in context, we compare it to Forget et al [9], who reported login times for 8-character text passwords as well as Persuasive Text Passwords (PTPs). 2 In the PTP variant that provided the optimal combination of security and usability, the login time was 17.1 sec.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…The proposed system uses the idea of Graphical password mechanism [3] with a series of images used for accessing the system. System provides graphics for authentication.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…The take-a-tail method may be viewed as a variant on previously proposed password strengthening schemes. Forget et al [18], randomly interleave system-generated characters into a password. The user may request a reshuffling of these characters until she obtains a password she regards as memorable.…”
Section: Related Workmentioning
confidence: 99%